Training of the management personnel for managing social institutions according to Master's programs: theoretical and methodological substantiation and IT support - Luniachek, V. (Problems of Engineer-Pedagogical Education, 2019)
The paper deals with the issues of training managerial staff for managing the social sphere according to master's programs. For the first time, a comprehensive overview of the issue of training executives working as deputy heads of regional and district state administrations, deputy mayors for social issues, heads of institutions of the social sphere, etc. is offered. It is proved that the practice of training and ongoing work of these leaders as representatives of one area of the social sphere does not allow them to fully see a number of problems within their functional responsibilities, which leads to certain distortions in social policy and requires appropriate integrated training. The paper analyzes the concept of "a social institution" as a complex entity and proposes its decomposition based on a systematic approach. In accordance with the provisions of the management theory, the author defines the concept of "social institution management". In addition, the necessity of further scientific and methodological substantiation of the conceptual and terminological field in the area of social institution management is proved to be a condition for further improvement of the management of this area as a whole. Based on the analysis of the website "Dysertatsii Ukrainy" ("Theses of Ukraine"), it is shown that the majority of theses defended in the field of social institution management relate to general secondary and higher education institutions as well as health care institutions. Such an important area as management of social care institutions remains largely out of the scientific community's attention. The work also analyzes the contingent of applicants for the master's program in specialty 073 "Management" in the educational program "Social institution management" in 2018 and 2019 and draws a conclusion about the approaches to meaningful content creation of the relevant educational program. Specifically, the authorial education curriculum is offered. Much attention is paid to substantiating the need to develop full-fledged courses in the Moodle virtual learning environment, taking into account the age ratio and specificity of the graduate students' professional activity.